Proposal to reduce the carbon footprint for building constructions. Study Case: Basic Sciences Building of the Technical University of Ambato, Ecuador. - Naranjo Rea, Esteban (2022)
Carbon dioxide is one of the most relevant greenhouse gases for preserving habitable temperatures in the Earth's atmosphere, however, the concentration of this type of gas has exceeded conventional levels, threatening life on the planet. The construction industry contributes enormously to CO2 and greenhouse gas emissions, both for the life cycle of its materials and for the operation and maintenance of the infrastructure, which is why it is imperative to search new materials and construction methods. that fulfill their primary function and at the same time reduce environmental pollution. For this project, the construction process of the Basic Sciences building of the Technical University of Ambato was taken as a basis and it has been divided into two stages: 1) Data Collection Plan: Gathering of structural information and emission factors of equivalent carbon dioxide; and 2) Information Processing and Analysis Plan: structural modeling, calculation of Work volumes and estimation of carbon footprints. Finally, an improvement proposal was made through the change of materials corresponding to non-structural items with high contamination for others that are more environmentally friendly and finally the correct static and dynamic functioning of the structure was verified. A reduction of 116.34 tons of carbon dioxide equivalent to 8.50% of the initial proposal was obtained, simultaneously ensuring faithful compliance with the structural and service performance of the building. Artículo recibido: 20 de septiembre de 2021 Artículo aceptado: 10 de diciembre 2021